Therapeutic Role of Green Tea on Human Body Function, Some Diseases and Weight loss: A Review - Sawsan Al-Harbi; Fouad Gatea (The Iraqi Journal of Medical Sciences)
After water, tea is the most consumed nutrient on the planet. However, black tea accounts for 78% of global tea consumption, while green tea accounts for only 20%. Except for flavored tea, all types of tea are made from the dried leaves of the tea bush. The type of tea is determined by the degree of oxidation of the leaves. Unoxidized tea leaves are used to make tea leaf, which is one of the less processed varieties of tea. It therefore, contains the most powerful antioxidants and beneficial polyphenols. Green tea polyphenols include epigallocatechin gallate (EGCG), epicatechin gallate, epicatechins, and flavanols, all of which are being studied in the lab for their potential in vivo effects. Kaempferol, quercetin, and myricetin are three types of flavonoids found in various parts. Although the caffeine in green tea can improve mental alertness, there is only weak, inconclusive evidence that it reduces the risk of most cancers or cardiovascular diseases, and there is no evidence that it aids weight loss. Using green tea as a health supplement has been linked to a slight improvement in general well-being. In a 2020 review, the Cochrane Collaboration identified a few potential negative effects, including gastrointestinal issues, higher levels of liver enzymes, and, more rarely, insomnia, elevated blood pressure, and skin reactions. Its anticancer and anti-inflammatory properties are well-known. Catechins are the main antioxidant dealers among the biologically active compounds found in Camellia sinesis. According to recent medical studies, the presence of function structural agencies and the range of hydroxyl agencies have a major impact on catechins' antioxidant activity. Unfermented inexperienced tea is the best source of those compounds. The review on green tea and its catechins focused on language literature in English. The literature search was conducted in the following databases: Pubmed (1997-2020), EMBASE (1997-2020), Allied and complementary Medicine Database (AMED, 1997-2020) and China Journals Full Text Database (1997-2020). The keywords used were selected from the following terms: green tea, catechins, anticancer, diabetes, polyphenols, in vivo studies, general pharmacology and toxicology. The health benefits and adverse effects of green tea and its catechins were reviewed. Keywords Green Tea, Human, diseases, weight loss Citation Al-Harbi SJ, Gatea FK. Therapeutic role of green tea on human body function, some diseases and weight loss: A review. Iraqi JMS. 2023; 21(1): 1-10. doi: 10.22578/IJMS.21.1.1